Leader, Knowing, Seeing, Being: Jonathan Edwards, Emily Dickinson... - Minkema, Kenneth P. (Jonathan Edwards studies, 2016)
Leader, Jennifer L. Knowing, Seeing, Being: Jonathan Edwards, Emily Dickinson, Marianne Moore, and the American Typological Tradition. Amherst and Boston: University of Massachusetts Press, 2016. Pp. x, 247. The great age for studying American typology was during the 1960s and ‘70s, and Jonathan Edwards received more than passing attention as part of that surge in interest, primarily among literary historians. They were attracted to Edwards’ natural typology and to his efforts to revivify and expand the ancient discipline of finding types or adumbrations and antitypes or fulfillments between the testaments of Scripture. While some scholars continue in that vein, there has been a definite downturn in the number of studies looking at Edwards in this time-tested way, which more often than not tied him to the Transcendentalists. More recently, examinations of Edwards’ typology have come in the context of semiotics, cultural-linguistic turns, the nature of rhetoric, stylometrics, and related approaches. Such treatments, however, are far outweighed nowadays by those that look at Edwards, first, as a student of the Bible, and second, as an inheritor of (or apostate from) Reformed orthodoxy.